A sandwich structure realizing the connection of CFRP and Al sheets using magnetic pulse welding. (1st September 2022) - Liu, Quanxiaoxiao; Wang, Shaoluo; Li, Guangyao; Cui, Junjia; Yu, Yang; Jiang, Hao
Abstract: A sandwich structure applied to joining carbon fiber reinforced plastics (CFRP) and AA5052 aluminum alloy sheets through magnetic pulse welding (MPW) was proposed. Mechanical properties, interfacial characteristics, joining and failure mechanisms of the CFRP/AA5052 MPW joints were explored. Results showed that the effective weld of a single spot was a closed annular region. Range of suitable collision angle and velocity to form an effective weld was 6° to 21° and 395 m/s to 330 m/s, respectively. Width of the effective weld was negatively correlated with the change rate of the collision angle; the faster the change rate of the collision angle, the narrower was the effective weld width. Difference of weld width, average collision velocity, and interfacial morphology resulted in uneven strength distribution of the annular weld. The two straight regions with greater weld strength were the main bearing regions. The number and distribution of welding spot had a great influence on mechanical properties of Al/CFRP joints. The more the number of welding spot, the stronger was the bearing capacity and the better was the energy absorption effect of the joints. In practical applications, the welding spot arrangement perpendicular to the load direction should be preferred because its energy absorption effect was better than the spot arrangement parallel to the load direction. Difference in failure mechanism between horizontal and vertical double-hole joints was mainly owing to the difference of the main stress states when the corresponding solder joints failed.